Military Migrants: Luxembourgers in the Colonial Army of the Dutch East Indies. Issue 3 (12th December 2017) - Bosma, Ulbe; Kolnberger, Thomas
Abstract : Among the roughly 150, 000 soldiers sent to the Dutch East Indies between 1815 and 1914, the Luxembourg contingent made up a tiny minority of just 1, 075 men. Based upon extensive research into their careers, data on these soldiers provide further clues to understanding what drove Europe's young men to become colonial soldiers. The results of this national case study will be compared with earlier investigations by Bossenbroek and Bosma on recruits for the Dutch colonial army. Similar to the Dutch soldiers, their Luxembourg counterparts had a predominantly urban provenance. However, in contrast to the Dutch, they did not have a strong military background, and it appears that fewer Luxembourgers stayed behind in the Dutch East Indies after their tour of duty. They were more attracted by the payments that the recruiters doled out in advance, particularly at a time of economic crisis, than in a career in the tropics.